Analysis of factors influencing the appearence of pharyngeal cancer in the world population (Research, Society and Development, 2020)
Objetive: Analyze and describe the factors that influence the emergence of pharyngeal cancer in the world population through a literature review. Methodology: Refers to a qualitative study, developed through a bibliographic review in the scientific eletronic library online databases (SCIELO) and EBSCOHOST FACULDADE SANTA MARIA (EBSCOHOSTFSM). Employing the subsequent inclusion parameters: full articles and publications by 2016 to 2020 in Portuguese, English and Spanish, using the descriptors: Throat cancer and pharynx cancer. Results: The articles and journals used in this research where published between 2016 and 2020, being 2 of the year 2020, being 2 of the year 2016 (12,5%), 5 of the year 2017 (31,25%) 5 of 2018 (31,25%) 2 of 2019 (12,5%) and 2 of 2020 (12,5%), totaling 16 articles used in this research. It was found that tabacco use, the alcoholism and HPV are influential factors in the appearance of pharyngeal cancer, besides oral cavity and head and neck region. Conclusion: Pharyngeal cancer has a significant importance due to its incidence and mortality rate worldwide, mainly in men. What influences the emergence of thoses neoplasias is the practice of smoking tabacco, alcoholism and HPV infection.